Struktur Fonologis Nama Orang Minangkabau - Reniwati Reniwati; Noviatri Noviatri; Rona Almos (Universitas Andalas, 2013)
Name of the Minangkabaunese has its own characteristics which can be recognized through the phonological structure. This article describes the number of word length Minangkabau name, the number of syllables, and the nature of each syllable of the name. There are three methods and research techniques used in this study: providing data, data analysis, and presentation of analysis results. Based on the number, the phonological structures of the Minangkabaunese names have two tendencies. First, people over 43 years old tend to consist of 1 (one) word name. In contrast, less than 44 years old tend to consist of two words name. Based on the number of syllables, the Minangkabaunese names also have two tendencies. First, over 43 years old the name tends to consist of three (3) syllables followed by a name consisting of 2 (two) syllables. The name of the Minangkabau people under 44 years are more varied, there consist of 2 to 5 syllables, some of them consisting of 6 to 7 syllables. Furthermore, the long name is not found Minangkabau consisting of one syllable and exceeds 7 syllables. Finally, based on the nature, there are two properties of syllables in the Minangkabaunese name which are closed syllables and open syllables.